C.P.S. Rugby Squad - Frank Aston::::::photographer::: (1911)
Group portrait of rugby team on field; with coach Chester Rubel (standing, left) and coach McHenry (standing, right); main buildings in background; Published in Polytechnic J. (v.7, no.1, Dec. 1911) with caption 'Foot-Ball Squad' and members identified